Analisa Debit Andalan Pada Das Batang Arau Dengan Menggunakan Model Soil And Water Assessment Tool (SWAT) - Maryam Afifa -; Afla Dina -; Elvi Roza Syofyan; Wisafri - - (Jurnal Ilmiah Poli Rekayasa, 2020)
Batang Arau is one of the rivers that flows in the city of Padang, the upstream part of the Batang Arau watershed starting from the Lubuk Paraku river which is in the northeast of Padang City, with a water catchment area of 2,504 hectares which is Dr. Muhammad Hatta, Nature Reserve Area Barisan I and Arau downstream. The Batang Arau watershed has decreased its primary forest area due to the large number of additional settlements. The increase in residential area resulted in the land that was previously not waterproof. The mainstay discharge always increases in the rainy season and decreases in the dry season. The mainstay discharge in the Batang Arau watershed is calculated using the Fj Mock method. The Batang Arau watershed also knows the mainstay discharge that occurred in 2010, 2012 and 2018 using the Soil and Water Assessment Tool (SWAT) model. The analysis was obtained from four processes, namely delineation of the watershed, the formation of the Hydrologic Response Unit (HRU), the formation of climatological data, and the simulation process. For the HRU analysis of the Batang Arau watershed, it was obtained 7 sub-watersheds, the dominant HRU, namely primary dryland forest, was 74.68%.